Project G-SPACE: protocol for exploring the influence of green space on sleep and mental health among children - Diana S. Grigsby-Toussaint; Jong Cheol Shin; Aliana Rodriguez Acevedo; William Kemball-Cook; Diane Story; Abby Katz; Ugoji Nwanaji-Enwerem; Gabrielle Evans; Azia Johnson; Brooke Ury; Yaideliz M. Romero-Ramos; Jue Yang; et al. (BMC, 2024)
Abstract Background The prevention of pediatric mental health disorders is a growing health priority in the United States. While exposure to green space, such as outdoor vegetation, has been linked with improved mental health outcomes in children, little is known about the impact of green space on children's sleep. Sleep has many benefits, but the factors affecting both sleep and mental health as they relate to green space exposure are not well understood in children. This study aims to investigate how green space can affect sleep in children and contribute to the promotion of mental health and wellbeing. Methods Project Green Space, Sleep, and Mental Health (G-SPACE) aims to recruit 250 elementary school-children from first, second, and third grade in Rhode Island to examine the influence of green space exposure on sleep, physical activity, and mental health over a five-year period. Objective measures of sleep, physical activity, and daily activity space will be assessed using an actigraph and a GPS (Global Positioning System) unit. Subjective measures of sleep duration, sleep quality, and mental health will be assessed using daily sleep diaries from parents, in addition to a range of survey items, including PROMIS® (Patient Reported Outcome Measurement Information System) pediatric scales, and the Children's Sleep Habits questionnaire, among others. Green space exposure will be based on measures of green space from the normalized difference vegetation index (NDVI) aligned with the daily activity trajectory of children. Additionally, saliva and DNA samples will be collected to examine epigenetic mechanisms linking green space to sleep and mental health. A subset of participants (n = 50) will be followed longitudinally to evaluate the long-term impact of green space on sleep and mental health among children. Multi-level models will be used to assess the association between green space exposure, sleep behaviors, and mental health. Discussion Project G-SPACE will evaluate whether green space utilization influences sleep and mental health in early elementary school children, and the possible mechanistic pathways through which these associations emerge.